The Digital Shadow in the ICU: An Interdisciplinary Narrative Review of Data Curation, Ethical Stress, and the Sociotechnical Workflow of Critical Care - Alotaibi, Hadi Munawer A; Hassan Husain Daghas; Majed Hifthallah Hakami; Yahia Abdullah Monawar Mubarak; Mariam Abdullah Alghamdi; Mohamad Bader Almotiry; Omar Mohammed Hawas Alruwaili; Norah Mohammed H Alruwaili; Ali Awwad Alharthi; Saeeda Hanen Sofyani; Ahmed Ghazi Alotaibi; Sultan Abdullah Alzahrani (Saudi Journal of Medicine and Public Health, 2024)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The modern Intensive Care Unit (ICU) is a nexus of intensive, multi-source data generation, creating a vast "digital shadow" of the patient that exists alongside the formal medical record. The labor involved in curating this shadow—filtering, interpreting, and transcribing data from devices, labs, and observations—is largely hidden. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review aims to examine how the invisible data-management practices of nurses, medical secretaries, and lab technicians shape the official narrative of critical illness, and to explore the resulting sociological and ethical implications for the care team. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive search of PubMed, CINAHL, Scopus, and Sociological Abstracts (2010-2024) was conducted, integrating literature from critical care, health informatics, science and technology studies (STS), and the sociology of work. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The review identifies a pervasive "curation gap" between raw data and the formal record. This gap is filled by distributed, often undervalued labor that distributes ethical stress, creates hierarchies of data credibility privileging technological over narrative knowledge, and can lead to communication fissures impacting care coordination. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Recognizing and formally integrating the sociotechnical work of data curation is essential for humanizing ICU care, mitigating moral injury among staff, and designing EHRs that support, rather than obscure, collaborative sense-making.